2006
DOI: 10.17221/3945-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The quality comparison of eggs laid by laying hens kept in battery cages and in a deep litter system

Abstract: At present there are important changes in housing systems in laying hen husbandry. Henceforward, only alternative husbandry systems shall be allowed, among which deep litter systems can be included. Therefore, many authors are engaged in the investigation of alternative systems, their advantages and disadvantages.Savory (2004) stated that from the welfare viewpoint cage systems were burdened with a lack of space for laying hens, however, conversely they ensured the better health status of laying hens. Peterman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 17 publications
3
8
2
3
Order By: Relevance
“…In the first experiment darker yolks were produced in cages while in the second these were from hens on litter. The results of the second experiment, where darker yolk colour was in eggs from litter, are in agreement with those of Sűto et al (1997), Pištěková et al (2006) and Singh et al (2009). The yolk colour depends mainly on pigments in feed but the same feed mixtures were used in both experiments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the first experiment darker yolks were produced in cages while in the second these were from hens on litter. The results of the second experiment, where darker yolk colour was in eggs from litter, are in agreement with those of Sűto et al (1997), Pištěková et al (2006) and Singh et al (2009). The yolk colour depends mainly on pigments in feed but the same feed mixtures were used in both experiments.…”
Section: Discussionsupporting
confidence: 90%
“…Data from a number of studies revealed differences in egg quality depending on the housing system. Moorthy et al (2000), Leyendecker et al (2001a) and Jenderal et al (2004) reported higher egg weights in cages, while Tůmová and Ebeid (2005), Pištěková et al (2006), Zemková et al (2007) found out heavier eggs on litter. Quality traits such as egg shell thickness, Haugh unit score and yolk index were reported to be higher in cages than on litter (Roland et al, 1997;Moorthy et al, 2000;Tůmová and Ebeid, 2005;Lichovníková and Zeman, 2008).…”
mentioning
confidence: 95%
“…Some studies indicated that egg weight was higher in cage systems than in floor systems or free-range systems (10). However, in some other studies, heavier eggs were found in litter systems than in cages (11,12). In the present study, eggs from the FR system were heavier than those from the CC and EC systems.…”
Section: Discussioncontrasting
confidence: 58%
“…Several studies were done in order to evaluate the effect of housing systems on eggshell quality including cages and litter systems, and to indicate which housing system is more effective for better eggshell quality. Pištěková et al (2006), Zemková et al (2007) and Singh et al (2009) detected heavier eggs on litter, whereas Moorthy et al (2000), Leyendecker et al (2001a); Lichovníková and Zeman (2008) and Tůmová et al (2011) found heavier eggs in cages. Hidalgo et al (2008) showed the effect of housing on the eggshell thickness and the strength, they stated that the shell thickness was the lowest in eggs produced in cages, while barn eggs presented the highest values.…”
Section: Introductionmentioning
confidence: 93%
“…Hidalgo et al (2008) showed the effect of housing on the eggshell thickness and the strength, they stated that the shell thickness was the lowest in eggs produced in cages, while barn eggs presented the highest values. On the other hand, Pištěková et al (2006) suggested that difference in the shell strength in eggs from deep litter system and in eggs from cage system was not found statistically significant. Pores density was higher in cage system than on litter (Tůmová et al, 2011).…”
Section: Introductionmentioning
confidence: 95%